Can a start-up establish international industry standards? The international development of a data solution platform in car parts business - Maria Elo (Inderscience Enterprises Ltd., 2025)
The study presents an international new venture based on car part data and intelligence examining its unique internationalisation process. The impact of the industry network in which the start-up is embedded is central in this international expansion, it plays a crucial role in the expansion process where a small start-up develops an international industry standard. Becoming the establisher of the dominant design is analysed from the perspective of collective internationalisation using an explorative case study approach. The findings illustrate particular characteristics of multiple entrepreneurial activities, the power constellation required for the process, the role of innovation as one key driver and the value creation logic. The study contributes to the understanding of contemporary accelerated internationalisation, its multifaceted character and industry standards.